Unforced errors and error reduction in tennis, I - Brody, H. (British Journal of Sports Medicine, 2002)
A typical tennis player will lose many more points through errors than through winners hit by the opponent. Only at the highest level of tennis is the number of winners comparable to the number of unforced errors. There are a number of ways in which a player's error rate can be reduced. This is explained here.